Spinal and supraspinal control of motor function during maximal eccentric muscle contraction: Effects of resistance training - Per Aagaard (Elsevier, 2018)
Neuromuscular activity is suppressed during maximal eccentric (ECC) muscle contraction in untrained subjects owing to attenuated levels of central activation and reduced spinal motor neuron (MN) excitability indicated by reduced electromyography signal amplitude, diminished evoked H-reflex responses, increased autogenic MN inhibition, and decreased excitability in descending corticospinal motor pathways. Maximum ECC muscle force recorded during maximal voluntary contraction can be increased by superimposed electrical muscle stimulation only in untrained individuals and not in trained strength athletes, indicating that the suppression in MN activation is modifiable by resistance training. In support of this notion, maximum ECC muscle strength can be increased by use of heavy-load resistance training owing to a removed or diminished suppression in neuromuscular activity. Prolonged (weeks to months) of heavy-load resistance training results in increased H-reflex and V-wave responses during maximal ECC muscle actions along with marked gains in maximal ECC muscle strength, indicating increased excitability of spinal MNs, decreased presynaptic and/or postsynaptic MN inhibition, and elevated descending motor drive. Notably, the use of supramaximal ECC resistance training can lead to selectively elevated V-wave responses during maximal ECC contraction, demonstrating that adaptive changes in spinal circuitry function and/or gains in descending motor drive can be achieved during maximal ECC contraction in response to heavy-load resistance training. Keywords: Corticospinal excitability, Eccentric muscle contraction, H-reflex, Neuromuscular plasticity, Resistance training, V-wave